Evaluation of Yogurt Microstructure Using Confocal Laser Scanning Microscopy and Image Analysis. Issue 6 (8th May 2015) - Skytte, Jacob L.; Ghita, Ovidiu; Whelan, Paul F.; Andersen, Ulf; Møller, Flemming; Dahl, Anders B.; Larsen, Rasmus
Abstract The microstructure of protein networks in yogurts defines important physical properties of the yogurt and hereby partly its quality. Imaging this protein network using confocal scanning laser microscopy (CSLM) has shown good results, and CSLM has become a standard measuring technique for fermented dairy products. When studying such networks, hundreds of images can be obtained, and here image analysis methods are essential for using the images in statistical analysis. Previously, methods including gray level co‐occurrence matrix analysis and fractal analysis have been used with success. However, a range of other image texture characterization methods exists. These methods describe an image by a frequency distribution of predefined image features (denoted textons). Our contribution is an investigation of the choice of image analysis methods by performing a comparative study of 7 major approaches to image texture description. Here, CSLM images from a yogurt fermentation study are investigated, where production factors including fat content, protein content, heat treatment, and incubation temperature are varied. The descriptors are evaluated through nearest neighbor classification, variance analysis, and cluster analysis. Our investigation suggests that the texton‐based descriptors provide a fuller description of the images compared to gray‐level co‐occurrence matrix descriptors and fractal analysis, while still being as applicable and in some cases as easy to tune.